Blended learning in physical education of distance students - Akhmatgatin, Anvar Amirovich; Struganov, Sergey M.; Balashov, Alexander V. (Физическое воспитание и студенческий спорт)
This article presents the features of mastering the academic discipline “Physical Education and Sport” by university distance students, as well as problems related to its teaching. Some trends in the development of educational systems related to the use of information technologies, in particular, distance learning and a blended form of organization of the educational process, as the most promising, are considered. It was assumed that the use of blended learning would ensure an increase in the success of solving educational problems of the discipline “Physical Education and Sport”, taught to distance students. To test this assumption, a pedagogical experiment was conducted, in which distance students participated, divided into control and experimental groups of 20 people each. In the experimental group, the educational process was organized using blended learning, in the control group – in the traditional form. During this pedagogical experiment, it was found that distance students who mastered the discipline “Physical Education and Sport” using the blended form of education showed better theoretical knowledge, as well as methodological and practical skills in the field of physical culture and sports compared to the distance students who mastered it in the traditional way. As a result of the conducted research, high efficiency of blended learning in mastering the academic discipline “Physical Education and Sport” by distant students has been established.